Let: $F(x)=\int_{\sin x}^{\cos x}e^{t^{2}+xt}\,dt$. Compute $F^{'}(0)$.

I tried the following: $F(x)=\int_{a}^{\cos x}e^{t^{2}+xt}\,dt - \int_{a}^{\sin x}e^{t^{2}+xt}\,dt$ where $a$ is between $\cos x$ and $\sin x$. Then I applied the second Fundamental theorem of Calculus to get: $F^{'}(x)=e^{\cos^{2}x+x\cos x}-e^{\sin^{2}x+x\sin x}$ and Hence $F^{'}(0)=e-1$. But in the book, the given solution is : $\frac{e-3}{2}$. Can anyone tell me what's wrong with my proof and give me the correct solution?

  • $\begingroup$ Do you mean to have the $x$ in the exponent in the integrand? $\endgroup$ – Joe Johnson 126 Jan 26 '12 at 22:10

$$F(x)=\int_{\sin x}^{\cos x}e^{t^{2}+xt}\,dt$$

To compute $F^{'}(0)$ let's use my latest derivation (applied to $a(x)=\sin x$, $b(x)=\cos x$, $h(x,t)=t^2+xt$) :

$$F'(x)=\int_{a(x)}^{b(x)}\frac{\partial h(x,t)}{\partial x}.e^{h(x,t)}dt+b'(x)e^{h(x,b(x))}-a'(x)e^{h(x,a(x))}$$

So that $$F'(0)=\int_{sin(0)}^{cos(0)}t.e^{t^2+0t}dt-\sin(0)e^{cos(0)^2+0\cos(0)}-\cos(0)e^{\sin(0)^2+0\sin0))}$$

or $$F'(0)=\int_0^1 t.e^{t^2}dt-1=\frac{e^{t^2}}2|_0^1-1=\frac{e-3}2$$


For convenience I use $x$ as the variable of integration. Let $$ F(t)=I(u(t),v(t),t)=\int_{u(t)}^{v(t)}f(x,t)dx $$

You have variable limits and need to differentiate under the integral sign. By the Leibniz integral rule, the derivative is

$$\begin{eqnarray*} F^{\prime }(t) &=&\frac{\partial I}{\partial t}\frac{dt}{dt}+\frac{\partial I }{\partial v}\frac{dv}{dt}+\frac{\partial I}{\partial u}\frac{du}{dt} \\ &=&\int_{u(t)}^{v(t)}\frac{\partial f(x,t)}{\partial t}dx+f(v(t),t)v^{\prime }(t)-f(u(t),t)u^{\prime }(t). \end{eqnarray*}$$

Hence $$ F^{\prime }(0)=\int_{u(0)}^{v(0)}\left. \frac{\partial f(x,t)}{\partial t} \right\vert _{t=0}dx+f(v(0),0)v^{\prime }(0)-f(u(0),0)u^{\prime }(0). $$

In the present case $$ \begin{eqnarray*} u(t) &=&\sin t,\qquad u(0)=0 \\ u^{\prime }(t) &=&\cos t,\qquad u^{\prime }(0)=1 \\ v(t) &=&\cos t,\qquad v(0)=1 \\ v^{\prime }(t) &=&-\sin t,\qquad v^{\prime }(0)=0. \end{eqnarray*}$$

and $$ \begin{eqnarray*} f(x,t) =e^{x^{2}+xt}, \qquad f(1,0) =e, \qquad f(0,0) =1. \end{eqnarray*}$$

So $$ F^{\prime }(0)=\int_{0}^{1}\left. \frac{\partial f(x,t)}{\partial t} \right\vert _{t=0}dx+0-1 $$

Since $$ \left. \frac{\partial f(x,t)}{\partial t}\right\vert _{t=0}=\left. \frac{ \partial }{\partial t}e^{x^{2}+xt}\right\vert _{t=0}=xe^{x\left( x+t\right) }\vert _{t=0}=xe^{x^{2}} $$

and $$ \int_{0}^{1}xe^{x^{2}}dx=\frac{1}{2}e-\frac{1}{2} $$

we finally get $$ F^{\prime }(0)=\frac{1}{2}e-\frac{1}{2}-1=\frac{1}{2}e-\frac{3}{2}. $$

You find another example here.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.